Judge and international custom = Juge et la coutume internationale - Lijnzaad, Liesbeth; Council of Europe (Leiden, The Netherlands : Brill Nijhoff, 2016)
International custom remains one of the most important sources of international law despite the codification of the law and the numerous international agreements concluded between the different actors of the international community. However, uncertainties still remain in relation to several of its aspects, presenting challenges to national and international judges when called upon to identify and apply the rules of customary international law. With a view to addressing these grey areas, the Council of Europe ad hoc Committee of Legal Advisers on Public International Law (CAHDI) in cooperation with the Ministry of Foreign Affairs of France organised a conference on "The Judge and International Custom" where important contributions were made by international and national judges clarifying some aspects of this topical issue. This volume contains these contributions, supplemented with articles commissioned by the CAHDI from some of the highest judges at international and national level. The collection highlights the valuable contribution made by the CAHDI to the development of public international law and in particular to the work of the International Law Commission and the Sixth Committee of the United Nations General Assembly by participating proactively in the legal debate to establish a well-defined international legal framework for this topical issue. --
Opposite pages have duplicate numbering.
Includes bibliographical references.
Parallel text in English and French on facing pages.
Keywords: Customary law, International; Judgments; International courts; Customary law, International; International courts; Judgments